RESPONSE OF CURRENT AREA DOSEMETERS TO NEW OPERATIONAL QUANTITIES. Issue 17 (4th August 2022) - Čemusová, Zina; Ekendahl, Daniela; Judas, Libor; Kapuciánová, Michaela; Kuča, Petr; Vykydal, Zdeněk
Abstract: New operational quantities for external radiation exposure presented by the ICRU brought changes, which can affect the use of current dosemeters. Dosemeters calibrated in the old quantities should be tested, and the results obtained should be analyzed with respect to the new quantities. The difference between the old and new quantities depends primarily on photon energy. This work concerns instruments for area monitoring, which were exposed to reference photon and neutron spectra of mean energies from 65 to 1250 keV and from 0.02 to 10 MeV, respectively. As expected, it was revealed that the current photon dosemeters overestimate the new quantity ambient dose. For the measurements within the energy interval chosen, it seems to be acceptable to implement a correction factor to optimize the response. For the purposes of measurements of photons of lower energies, further research would be needed. To adapt the response of the neutron dosemeter tested, recalibration or redesign can be considered, but no fundamental changes seem to be necessary for the investigated spectra.